Putting ITIL® Into Practice: Applying ITIL® 4 Foundation Concepts. - Pultorak, David (linkedin.com, 2019)
Move ITIL® principles into practice. Explore the seven ways framework for applying ITIL® Foundation concepts, with all new content for ITIL® 4.